Emotional Intelligence and its Relationship to Psychological Cohesion and Social Communication Skills among Students of the College of Physical Education and Sport Sciences at the University of Samarra - Hayder Abdulhafidh Shehab; Luay Naji Hamad; Bilal Salman Mahmoud (Institute of Medico-legal Publications Pvt Ltd, 2021)
The aim of this study is to identify the relationship between emotional intelligence, psychological cohesionand social communication skills among students of the College of Physical Education and Sport Sciences atthe University of Samarra, that is to identify a group of students from this college whose number was about(140) students through the use of the following: emotional intelligence scale prepared by psychologicalcohesion scale, social communication scale designed by and Statistical Package for Social Sciences(henceforth SPSS) was also used. Accordingly, the study deduced that students of the college of PhysicalEducation and Sport Sciences at Samarra University have a considerable level of emotional intelligencewhich was positively reflected in their social solidarity and social communication skills. For this reason, theresearcher recommends more expansion to clarifying the concept of emotional intelligence, psychologicalcohesion and social communication skills, as they are among the novel concepts in sports field.